Analisis Kelayakan Investasi Pembangunan Villa OHANA di Gianyar Bali Menggunakan Metode NPV, IRR, BCR dan Payback Period - Nur Afni Helia Dewi; Amri Gunasti (Journal of Science and Engineering, 2026)
The development of villas as a form of property invenstment in the tourism sector requires a financial feasiblity analysis to ensure that the investment provides optimal returns. Thid study aims to analyze the investment feasibility of the Villa OHANA development project located in Gianyar, Bali, using Net Present Value (NPV), Internal Rate of Returns (IRR), Benefit Cost Ratio (BCR), and Payback Period (PBP) methods. The data used in this study are based on the project’s cost estimation (RAB) with a total investment of IDR 2,195,318,339 and revenue assumptions derived from rental price and occupancy rate. The result show that the NPV is IDR 159,369,661, the IRR is 11.7% which is higher than the discount rate 10%, the BCR is 1.07 (>1), and the Payback Period is 5.73 years. Based on these results, it can be concluded that the Villa OHANA development project is financially feasible and profiable as an investment in the tourism property sector.